Vital statistics on Congress 2008 - Ornstein, Norman J. (Vital statistics on Congress, 2008)
Vital Statistics on Congress remains the quintessential source of authoritative information on America's legislature. This important series tracks the elements that define and describe Congress in the post-World War II era, and in this new edition, three of America's most esteemed political analysts extend their examination through the 109th Congress. They combine historical context with insightful analysis and copious data to produce a valuable and authoritative picture of the U.S. Senate and House of Representatives. Norman Ornstein, Thomas Mann, and Michael Malbin track the changing makeup o.